The political economy of oil in Nigeria: How oil's impact on rent distribution has contributed to Nigeria's sub-optimal economic performance - Ncala, Thembekile (School of Economics, 2017)
Nigeria is an oil-rich country, and one of the largest oil producers in the world, however, its economic and developmental statistics have consistently ranked among the worst in the world. This paradox is widely believed to be a result of the natural resource curse. The natural resource curse is a phenomenon attributed to the inverse relationship between economic growth rates and the natural resource abundance of countries, and several notions have been put forward as to the mechanism through which the curse arises. These notions are generally categorised as either market-based explanations or political economy-based explanations. However, market-based explanations rely on assumptions that often do not apply in developing countries such as Nigeria. Consequently, the literature has come to increasingly focus on political economy explanations, two of the most prominent of which are rent seeking, and domestic conflict and political instability. Therefore, this paper seeks to identify some the drivers of the curse in Nigeria by particularly assessing the influence that rent seeking and domestic conflict and political instability may have had on Nigeria's economic experience. Since much of the resource curse literature is based on quantitative analysis, this paper aims to extend the literature using a qualitative approach, which involves the process tracing of major events in Nigeria. This approach is motivated by the fact that qualitative analysis is better suited to the task of identifying crucial insights concerning underlying dynamics of a specific country. Furthermore, this paper uses the limited access order (LAO) framework to guide its analysis. This framework is useful given that it involves the analysis of rent distribution as a means of curbing violence. Therefore, overall, this paper focuses on deciphering how oil's impact on the nation's economic rent distribution contributes to Nigeria's economic performance. Rent distribution, which largely occurs through patronage and corruption in Nigeria, is analysed through two different dimensions: (i) Formal rent distribution, which is institutionalised, and which mainly involves examining oil influenced changes to the revenue allocation formula and (ii) less formal rent distribution, which primarily involves examining discretionary and covert rent distribution in the oil industry. Based on the analysis, this paper concludes that oil's impact on rent distribution contributes to Nigeria's substandard growth in two ways; directly and indirectly. Regarding the first dimension, the effect is indirect, as oil's impact on formal rent distribution becomes a driver of conflict, which in turn adversely affects the economy's growth performance. However, regarding the second dimension, the effect is more direct, because oil's impact on discretionary rent distribution leads to massive economic waste, which contributes to the suboptimal growth of Nigeria's economy. Overall, with the lack of good institutions that can limit the power of the federal government, and effectively enforce checks and balances in the oil sector, Nigeria's experience of conflict and economic underperformance will remain perpetual in nature.